Network Pharmacology Study on the Mechanisms of Panax Notoginseng in the Treatment of Diabetic Retinopathy and Cataract - Ting Zhang; Guangquan Ji; Tianpu Feng; Xi Lin; Lei Wang; Yi Xu; Pan Shi; Wenxue Liang (Applied Bionics and Biomechanics)
Conclusion: These findings provide insights into the molecular-level action of P. notoginseng against these diseases. Overall, this study enhances our understanding of the potential of P. notoginseng in treating DR and DC as comorbidities and establishes a foundation for further research.